Case Report: Rare intraventricular H3 K27-altered diffuse midline glioma in an adult - Jasso, Merari; Zhu, Jay-Jiguang; Bhattacharjee, Meenakshi B.; Hergenroeder, Georgene W. (Frontiers in Oncology, 2025)
H3 K27-Altered Diffuse Midline Gliomas are commonly found in children and adolescents in midline locations such as the thalamus, brain stem, and spinal cord. It is rare for these tumors to affect adults and to occur in locations like the lateral ventricles. Despite aggressive treatment methodologies, there is no cure for this disease. The median survival is between 8-12 months. A 24-year-old white male presented to the emergency department due to severe headache refractory to pain medications with a 2-month history of progressive headaches and eventual memory problems. Computed tomography (CT) and magnetic resonance imaging (MRI) showed an intraventricular enhancing mass and hydrocephalus. The final diagnosis was an intraventricular H3 K27-Altered Diffuse Midline Glioma. The patient underwent two craniotomies, one laser interstitial thermal ablation (LITT), chemoradiotherapy, and bevacizumab and ONC206, through compassionate use. Despite a reduction in the tumor size, it continued to spread to other brain areas, leading to further complications and, eventually, his death, 10 months after initial diagnosis. From review of the literature, 21 cases were identified, and the median age was 24. Their median survival is 10.5 months (ranges 1 - 24 months). This case report presents the clinical, radiological, pathological, and molecular characteristics of a 24-year-old white man diagnosed with a ventricular H3 K27-Altered diffuse midline glioma, highlighting the rare presentation, management, and outcomes.